The formative assessment as systematic practice in higher basic education students - Cobeña, Gema Tatiana Bravo; García, Lucía Atenaida Pin; Pin, Sandra Cristina Solís; Montes, Lubis Carmita Zambrano (International research journal of management, IT and social sciences, 2021)
In the educational field, evaluation is a widely used term but generally associated with qualification, measurement, or as a promotional item from year to year. So, it is essential to reflect on the use given to it, in educational contexts. The objective was to analyze the perspective of teachers and students to the formative evaluation and their contribution to the improvement of the teaching-learning process, of the tenth-year students of a Fiscal Educational Unit in the city of Manta. The quantitative method was applied, to gather the information, with the use of a web survey aimed at both. As a result, it was obtained to be applied through: rubrics, portfolios, observations, conceptual maps, essays, co-evaluation, self-assessment, feedback; but, it does so in an ascetic and intuitive way. It is concluded that the assessment must be carried out in a procession manner, where the development of superior skills is enhanced, with dynamic activities, that favor metacognition, and self-regulation in the educational process.